Pengaruh Lama Perlakuan Uap pada Serat terhadap Sifat Fisis dan Mekanis Papan Semen Serat Sisal Effect of Fiber Steaming Treatment on the Physical and Mechanical Properties of Sisal Fiber Cement Bonded Board - Ismail Budiman; Mohamad Gopar; Subyakto Subyakto; Bambang Subiyanto (Masyarakat Peneliti Kayu Indonesia, 2009)
The main problem of making Sisal fiber cement bonded board is how to mix fibers and cement to get excellent performance of board due to the presence of extractives. Steam treatment on fibers is expected to reduce extractives in the fibers; therefore it will improve the bonding between fibers and cement. Beside that, utilization of catalysts, such as calcium chloride (CaCl2) and magnesium chloride (MgCl2), is expected to increase the physical and mechanical properties of Sisal fiber cement bonded board. Fibers of Sisal was chopped into 0.5 1.0 cm of length. Steam treatment was conducted in autoclave for 30, 60 and 120 minutes at 1.15 atm of pressure and 121ºC of temperature, and untreated Sisal as control. Chopped fiber was dried in an oven at 60ºC to obtain 5% of moisture content. The content of CaCl2 or MgCl2 was 5% of cement weight.The board was produced at a dried fiber : cement ratio of 1 : 3 and water : cement ratio of 1 : 2 based on board weight. The target density of the boards produced was 1.25 g/cm3. Cement bonded Sisal fiber was formed into 25cm x 25cm x 1cm mat, and then cold pressed for 24 hours. Composites were conditioned at room temperature for 28 days. Physical and mechanical characteristics were tested by Universal Testing Machine (UTM). Results shown that combination of steam treatment and catalyst added improved the physical and mechanical properties such as thickness swelling (TS), modulus of elasticity (MOE), modulus of rupture (MOR), screw withdrawal (SW) and internal bond (IB).